Geomorphic Systems of North America 1987
DOI: 10.1130/dnag-cent-v2.119
|View full text |Cite
|
Sign up to set email alerts
|

Canadian Shield

Abstract: The Canadian Shield* (Fig. 1) is a geologically complex terrain that makes up about one-third of the North American landmass. Its rocks were deposited, formed, and deformed over a time span encompassing about three-quarters of the earth’s known geologic history. Consequently, it includes lithologies, structural elements, and topography as varied as those found on the North American continent as a whole. Because of the complexity of geomorphic features that reflect this geologic diversity, we have decided to fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 53 publications
1
18
0
Order By: Relevance
“…Here, pond and lake patterns can be either random or regular (for example, the polygonal tundra in the Lena Delta in Siberia or on the Barrow Peninsula in Alaska -Figures 2a,b). Regions such as the Canadian Shield that were glaciated during the late Pleistocene are mainly characterized by postglacial and proglacial waterbodies that typically form linear patterns (Figure 2e), which are the result of glacial scour, bedrock erosion, and glacial deposition (Shilts et al, 1987). Riverine systems such as the Mackenzie Delta in Canada, feature a highly interconnected hydrological network with flood-plains, oxbow lakes, and thermokarst ponds and lakes (Figure 2f).…”
Section: Study Regionsmentioning
confidence: 99%
“…Here, pond and lake patterns can be either random or regular (for example, the polygonal tundra in the Lena Delta in Siberia or on the Barrow Peninsula in Alaska -Figures 2a,b). Regions such as the Canadian Shield that were glaciated during the late Pleistocene are mainly characterized by postglacial and proglacial waterbodies that typically form linear patterns (Figure 2e), which are the result of glacial scour, bedrock erosion, and glacial deposition (Shilts et al, 1987). Riverine systems such as the Mackenzie Delta in Canada, feature a highly interconnected hydrological network with flood-plains, oxbow lakes, and thermokarst ponds and lakes (Figure 2f).…”
Section: Study Regionsmentioning
confidence: 99%
“…Previous work has demonstrated that the large scale pattern of eskers can be used to gain insights into the factors that control where and when they occur under an ice sheet (Aylsworth & Shilts, 1989a;Clark & Walder, 1994;Menzies & Shilts, 1996;Shilts, Aylsworth, Kaszycki, & Klassen, 1987). Various (and sometimes inter-relating) factors have been suggested as being an important control on the location and formation of eskers.…”
Section: Assessment Of the Factors That Control Esker Location And Fomentioning
confidence: 99%
“…The Precambrian Shield makes up about one-third of the North American landmass (Shilts et al, 1987). A large part of the Shield in central and eastern Canada was scoured by Pleistocene glaciation to expose gneissic and granitoid rocks, with glaciofluvial and lacustrine deposits partially infilling many depressions in the bedrock.…”
Section: Introductionmentioning
confidence: 99%